Tumors With Intrahepatic Bile Duct Differentiation in Cirrhosis: Implications on Outcomes After Liver Transplantation. Issue 1 (January 2015) - Facciuto, Marcelo E.; Singh, Manoj K.; Lubezky, Nir; Selim, Motaz A.; Robinson, Dorothy; Kim-Schluger, Leona; Florman, Sander; Ward, Stephen C.; Thung, Swan N.; Fiel, MariaIsabel; Schiano, Thomas D.
Abstract : Background: The role of liver transplantation (LT) in the management of cirrhotic patients with tumors exhibiting intrahepatic bile duct differentiation remains controversial. The objective of this study was to characterize the spectrum of these tumors and analyze post-LT outcomes. Methods: Retrospective pathology database search of explant histology analysis of liver transplants between April 1993 and November 2013. Results: Thirty-two patients were analyzed, 75% were men with a mean age of 60 years. Seven patients had nodules demonstrating intrahepatic cholangiocarcinoma (I-CCA), nine had I-CCA nodules occurring concomitantly with hepatocellular carcinoma (HCC), and 16 had mixed HCC-CCA nodules. The median number of tumors was 1 and size was 2.5 cm. Overall patient survival post-LT at 1 and 5 years was 71% and 57%, respectively. Patients within Milan criteria, especially with I-CCA features, showed a 5-year tumor recurrence rate (10%) and 5-year survival rate (78%) comparable with other patients having HCC within Milan criteria. Conclusion: This series showed that patients with CCA within Milan criteria may be able to achieve acceptable long-term post-LT survival. Abstract : Results of liver transplantation in 32 patients with intrahepatic cholangiocarcinoma with and without hepatocellular carcinoma show a five-year tumour recurrence rate of 10% for patients meeting the Milan criteria.